Different kinetics of infectious processes in vertebral osteomyelitis of pyogenic or tuberculous origin explain different timing of surgery. Issue 8 (2nd August 2020) - Perrineau, Ségolène; Zarrouk, Virginie; Zoghlami, Mohamed; Allaham, Wassim; Leflon-Guibout, Véronique; Rousseau, Marc-Antoine; Fantin, Bruno
Abstract: Background: Whether surgery modalities vary according to kinetics of pathological processes responsible for vertebral osteomyelitis (VO) is unclear. We therefore compared surgical modalities in patients with haematogenous pyogenic VO (HPVO) or tuberculous VO (TVO). Methods: Patients who had surgery for HPVO or TVO between January 1997 and June 2018 in a university hospital were included. Surgical indications, timing, and procedures and outcomes were evaluated at the end of treatment. Results: Seventy-eight patients (50 men) were included: 39 with HPVO and 39 with TVO; median age was 64 and 41 years, respectively. In patients with HPVO, surgery was performed early: 17 (44%) had surgery within 72 h of admission; main indication for surgery was neurological deficit in 29 patients that persisted in 12 patients (27%). In patients with TVO, surgery was performed later ( p <.001), after two weeks in 20 patients (51%), and was indicated by a neurological deficit in 23 patients; among them, only one (4%) had residual deficit. Conclusions: Different kinetic profiles of the infectious processes explain the more rapid indication for surgery in patients with HPVO and the more favourable neurological recovery in patients with TVO.